Effect of Urea and Cow Fecal Compost on Growth and Yield of Green Eggplant (Solanum melongena L.) - Ahmad Raksun; Mahrus Mahrus; I. Gde Mertha (Postgraduate, University of Mataram, 2021)
Eggplant (Solanum melongena L.) is a vegetable that grows well in various regions in Indonesia. Its growth is largely determined by the availability of nutrients in agricultural land. Research has been conducted on the effect of urea and cow fecal compost on the growth and yield of green fighting plants. This study aims to determine: (1) the effect of urea application on the growth and yield of green eggplant plants, (2) the effect of cow fecal compost application on the growth and yield of green eggplant plants, (3) the effect of the interaction of urea and cow fecal compost. on the growth and yield of green eggplant plants. This study used a 2-factor design. The first factor is the dose of urea fertilizer and the second factor is the dose of cow fecal compost. Growth parameters were stem height, leaf length, and leaf width, while yield parameters were the wet weight of green eggplant. The research data were analyzed using analysis of variance. The results showed: (1) differences in the dose of cow fecal compost had a significant effect on stem height, leaf length, and fruit wet weight but had no significant effect on leaf width of green eggplant, (2) differences in the dose of urea had a significant effect on the stem, leaf length, and leaf length and fruit wet weight but did not significantly affect leaf width of green eggplant, (3) the interaction between urea fertilizer treatment and cow compost did not significantly affect all growth parameters and yield parameters of green eggplant